2001
DOI: 10.2527/2001.79123034x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of free-choice vs mixed-ration diets on food intake and performance of fattening calves.

Abstract: Research findings and management recommendations typically emphasize responses of the "average" individual, yet more than half of the animals in a group may differ significantly from the mean regarding food preference and intake. The productivity of a herd may be adversely affected if animals differing from the mean are fed a uniform diet formulated to meet the needs of the "average" individual. We compared the intake and performance of beef calves offered a choice or no choice among foods. Diets consisted of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
49
5
4

Year Published

2005
2005
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(64 citation statements)
references
References 26 publications
6
49
5
4
Order By: Relevance
“…This result contrasts with those obtained by other researchers (Atwood et al, 2001;DeVries and von Keyserlingk, 2009;Moya et al, 2011). Atwood et al (2001) compared the intake of beef calves offered a choice or no choice among foods.…”
Section: Discussioncontrasting
confidence: 87%
See 4 more Smart Citations
“…This result contrasts with those obtained by other researchers (Atwood et al, 2001;DeVries and von Keyserlingk, 2009;Moya et al, 2011). Atwood et al (2001) compared the intake of beef calves offered a choice or no choice among foods.…”
Section: Discussioncontrasting
confidence: 87%
“…This result contrasts with those obtained by other researchers (Atwood et al, 2001;DeVries and von Keyserlingk, 2009;Moya et al, 2011). Atwood et al (2001) compared the intake of beef calves offered a choice or no choice among foods. Diets consisted of ad libitum access to either a chopped, mixed ration of forage (corn silage, 15.5%, and alfalfa hay, 18.9%) and concentrate (rolled barley, 31.3%, and rolled corn, 31.3%) or a choice among those foods offered individually, and they found that animals offered the mixed ration tended to eat more than animals offered a free choice.…”
Section: Discussioncontrasting
confidence: 87%
See 3 more Smart Citations